The intersection of disability status and rurality in American Indian/Alaskan Native communities - Mashinchi, Genna M.; Hicks, Emily C.; Leopold, Arin J.; Greiman, Lillie; Ipsen, Catherine (Frontiers in Rehabilitation Sciences, 2022)
There is a noteworthy gap in the literature regarding disability in rural American Indian/Alaskan Native (AI/AN) communities. This is significant, as many tribal lands are in rural areas and AI/AN individuals experience some of the highest prevalence rates of disability. To address this gap, we used descriptive statistics to examine the intersection of AI/AN and rurality in disability prevalence. Results indicate that rural counties have the highest prevalence of disability for both Whites and AI/ANs and that AI/ANs experience higher prevalence rates than Whites. However, further analysis indicates that county makeup (counties with high prevalence of AI/AN in the general population) moderated this relationship. Specifically, rural counties with populations of at least 5% AI/AN had lower prevalence of AI/AN disability compared to counties with populations with less than 5% AI/AN. Further analysis is needed to unpack this relationship, but results might suggest that AI/AN communities may feature resilient and protective attributes, moderating the amount of disability experienced in rural AI/AN communities.